Supercritical carbon dioxide extraction of red pitaya (Hylocereus polyrhizus) seeds: response surface optimization, fatty acid composition and physicochemical properties - Abdullah, Asiah; Abd Gani, Siti Salwa; Mohd Mokhtar, Nor Fadzillah; Hin, Taufiq Yap Yun; Abdul Haiyee, Zaibunnisa; Mustafa, Suhana (Malaysian Society of Applied Biology, 2018)
A new technology called supercritical fluid extraction (SFE) was performed to obtain oil from red pitaya (Hylocereus polyrhizus) seeds. The extraction process was optimised by response surface methodology (RSM) and the effects of extracting variables namely temperature (35-65ºC) and pressure (1500-5000 psi) were evaluated. A model was developed using central composite design (CCD) for the determination of optimum condition that gave highest oil yield. The highest oil yield was predicted to be about 6.93 wt%, under optimal conditions temperature of 47ºC and pressure of 4750 psi. At optimum conditions obtained, triplicate extractions were performed and found that average experimental extraction yield of oil was 6.88 ± 0.06% and in a good agreement with the predicted value. Gas chromatography mass spectrometry (GC-MS) analysis was carried out to identify the chemical composition of the oil and compared with n-hexane extracted oil. GC-MS analysis revealed negligible differences in fatty acid composition of oil extracted from both methods with linoleic acid as the major component. In the studies of oil quality, the important physicochemical properties of the extracted oil were also analyzed. © 2018, Malaysian Society of Applied Biology. All rights reserved.